PERANCANGAN GAME EDUKASI PETUALANGAN ANAK PRAMUKA DENGAN MENGGUNAAN SCIRRA CONSTRUCT 3 - Myju Anisa; Nur Rofiq (CV. Multi Kreasi Media, 2022)
Scouting is one of the activities carried out outside the school environment with the aim of forming personality, skills, intelligence, strength, social science and love for the homeland. Carrying out scout activities requires patience for every teacher / coach. Game is one of the means of entertainment media that is played during free time to relieve boredom, apart from being a means of entertainment, games can also be a means of learning media. Educational games are very appropriate to be used as learning media for elementary school age children when compared to conventional learning, educational games excel in several aspects. One of the advantages is that animation can improve memory so that children store subject matter for a longer time compared to conventional teaching methods. The author makes an Android-based educational game using game engine construct 3 and applies the waterfall method with the expectation that teachers and elementary school children can take advantage of games designed as learning media so that they are not bored in learning. With the Android system, of course, learning becomes easier because it can be done anytime and anywhere. The educational game designed is a learning application for elementary school children from the age of 8-11 years which contains an adventure educational game for scouts. It is expected to increase interest in learning.